The witness of religion in an age of fear - Kinnamon, Michael (Westminster John Knox Press, 2017)
We live in a world driven by fear. But should we allow fear to play such a large role in our lives? According to the religions of the world, the answer is no. In this helpful and illuminating book, Michael Kinnamon challenges readers to consider why we find ourselves in this age of fear and what we can do about it. Drawing on support from a diversity of religious traditions and teachers, Kinnamon argues that religious faith is the best way to combat a culture of fear. He explores fear in relation to the Israeli-Palestinian conflict and the American political scene, and he shares courageous examples of individuals from different religions working for peace. Perfect for individuals or group study, this book helps readers understand the manipulative power of fear and how religious beliefs call us to reject fear at all costs. A study guide is included. - from publisher.